2019
DOI: 10.1371/journal.pone.0210798
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candida administration in a Clostridium difficile mouse model worsens disease severity but is attenuated by Bifidobacterium

Abstract: Gut fungi may influence the course of Clostridium difficile infection either positively or negatively for the host. Fungi are not prominent in the mouse gut, and C. albicans, the major human gastrointestinal commensal yeast, is in low abundance or absent in mice. Bifidobacterium is one of the probiotics that may attenuate the severity of C. difficile infection. Inflammatory synergy between C. albicans and C. difficile, in gut, may provide a state that more closely resembles human infection and be more suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…Severity and outcome of CDI could finally be influenced by communities of gut inhabitants (or transient passengers) not addressed in the present study, such as gut fungi. Recently, it has been shown that oral Candida albicans administration in a C. difficile mouse model worsens disease severity, exacerbating several markers used to characterize the severity of CDI (i.e., mortality rate, weight loss, gut leakage, and serum and intestinal tissue cytokines), without increased fecal C. difficile or bacteremia detection [32].…”
Section: Discussionmentioning
confidence: 99%
“…Severity and outcome of CDI could finally be influenced by communities of gut inhabitants (or transient passengers) not addressed in the present study, such as gut fungi. Recently, it has been shown that oral Candida albicans administration in a C. difficile mouse model worsens disease severity, exacerbating several markers used to characterize the severity of CDI (i.e., mortality rate, weight loss, gut leakage, and serum and intestinal tissue cytokines), without increased fecal C. difficile or bacteremia detection [32].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro models C. albicans coculture promotes C. difficile and C. perfringens growth in aerobic conditions [63] C. difficile mouse model Oral Candida administration worsens C. difficile severity [64] Antagonistic In vitro models p-cresol, produced by C. difficile, inhibits hyphal formation and virulence of C. albicans [63] C. difficile mouse model C. albicans reduces C. difficile growth and C. difficile-related mortality, which appears dependent on the alterations that Candida induces on the gut bacteriome composition [40] https://doi.org/10.1371/journal.ppat.1008353.t001…”
Section: Synergymentioning
confidence: 99%
“…Although these studies suggest a protective role for C. albicans during CDI, other groups have reported opposite effects. Panpetch and co-workers recently reported that the presence of C. albicans during CDI increased virulence in a murine model [67]. In these studies, the authors introduced C. albicans one day before C. difficile infection and observed disease exacerbation presumably due to increased inflammatory responses [67].…”
Section: Discussionmentioning
confidence: 99%
“…Panpetch and co-workers recently reported that the presence of C. albicans during CDI increased virulence in a murine model [67]. In these studies, the authors introduced C. albicans one day before C. difficile infection and observed disease exacerbation presumably due to increased inflammatory responses [67]. The conflicting results from these murine studies are likely due to the timing of Candida acquisition.…”
Section: Discussionmentioning
confidence: 99%